Drywood termites in the Azores: Problems and tentative solutions - Nunes, L. (2009)
The detection in 2002 of drywood termites in the islands of Azores has became an urgent issue to be coped with given the fast degradation that structural elements can show after a short period of installation of a colony. A recent study indicates drywood termite presence in about half of the buildings of the historic centre of Angra do Heroísmo (a World Heritage site) in Terceira Island and timber structures surveys conducted so far points to strong levels of degradation of timber elements and structures. A strong effort should be put on the rehabilitation of structures already affected, implementation of control procedures for restraining the spread of new colonies into so far sound buildings and alteration of traditional practices (namely choice of wood species and protection treatments) regarding timber utilization in construction. This document presents some of the most relevant facts regarding drywood termites’ presence in the Azores, degradation problems already detected, research efforts in place and preliminary proposals already made to deal with this problem.